A universal automated complex for control and diagnostics of semiconductor devices and structures - Konakova, R.V.; Rengevych, O.E.; Kurakin, A.M.; Kudryk, Ya.Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
We present a universal automated complex for control and diagnostics. It is intended to measure static, pulse and capacitance-voltage characteristics of two- and three-terminal networks, both at room temperature and in 77-1000 K temperature range. A distinguishing feature of complex construction is the possibility for simulation of interrelation between parameters of the objects studied. The complex has been tested when studying the effect of g- and microwave radiations on parameters of gallium arsenide SB-FETs, GaN-based HEMTs and silicon carbide SBDs.